Mental Verbs in Marketing Texts: Systemic Functional Linguistics Perspectives - Bahtera Sembiring; Mulyati Khorina; Danny Gandana Nugraha (Muhammadiyah University of Mataram, 2021)
The aim of this study was to examine mental verbs found in Marketing texts. Thus, the qualitative data were taken from a graduate textbook entitled Selling Today. The data were analyzed by applying Systemic Functional Linguistics (SFL) framework. The results showed that mental process of like type appear to be dominant which is realized by various lexical verbs. The mental process occur on all types of mental clauses: perceptive, cognitive, desiderative, and emotive. However, among the four types of mental clauses, cognitive clauses has the highest occurance frequency with various choices of verbs realizing its mental process. The findings offer opportunity to model English grammar for Marketing students